Inhibition of prostate cancer growth using doxorubicin assisted by ultrasound-targeted nanobubble destruction - Fan X (Dove Medical Press, 2016)
Xiaozhou Fan,1,* Luofu Wang,2,* Yanli Guo,1 Xingyu Xiong,1 Lianhua Zhu,1 Kejing Fang1 1Department of Ultrasound, Southwest Hospital, 2Department of Urology, Daping Hospital, Third Military Medical University, Chongqing, People’s Republic of China *These authors contributed equally to this work Abstract: Ultrasound (US)-targeted microbubble destruction has been widely used as an effective drug-delivery system. However, nanobubbles (NBs) have better stability and stronger penetration than microbubbles, and drug delivery assisted by US-targeted NB destruction (UTND) still needs to be investigated. Our aim was to investigate the effect of doxorubicin (DOX) on the inhibition of prostate cancer growth under UTND. Contrast-enhanced US imaging of transplanted PC3 prostate cancer in mice showed that under a combination of 1 W/cm2 US power and a 100 Hz intermittent pulse with a “5 seconds on, 5 seconds off” mode, NBs with an average size of (485.7±33) nm were effectively destroyed within 15 minutes in the tumor location. PC3 cells and 20 tumor-bearing mice were divided into four groups: a DOX group, a DOX + NB group, a DOX + US group, and a DOX + NB + US group. The cell growth-inhibition rate and DOX concentration of xenografts in the DOX + NB + US group were highest. Based on another control group and these four groups, another 25 tumor-bearing mice were used to observe the treatment effect of nine DOX injections under UTND. The xenografts in the DOX + NB + US group decreased more obviously and had more cellular apoptosis than other groups. Finally, electron microscopy was used to estimate the cavitation effect of NBs under US irradiation in the control group, NB group, US group, and NB + US group. The results of scanning electron microscopy showed that PC3 cells in the DOX + NB + US group had more holes and significantly increased cell-surface folds. Meanwhile, transmission electric microscopy confirmed that more lanthanum nitrate particles entered the parenchymal cells in xenografts in the NB + US group compared with the other groups. This study suggested that UTND technology could be an effective method to promote drugs to function in US-irradiated sites, and the underlying mechanism may be associated with a cavitation effect. Keywords: ultrasound therapy, nanobubble, cavitation effect, prostate cancer